Bio-Based Oil As A New Rubber Processing Oil In Development Of Green & Sustainable Tire Tread Compound - Din, Muhamad Nur Iman Syafaat (Universiti Sains Malaysia, 2022)
The usage of processing oil in the tire industry is a common practice. The aim for this study is to produce bio-based processing oil that can lead to green and sustainable tire tread compound. Then the mechanical properties of the different compound consist of EPO and GT 3000 processing were compared, correspondingly. The process of synthesis palm oil lead to ring opening. The greater the number of epoxy rings that are opened as a result of the procedure, the greater the potential for crosslinking. Bio-based processing then being used in the compounding process to investigate the mechanical properties along with the rubber compound using mineral processing oil (hydrocarbon oil). The rubber compound were freeze for 24 hours before vulcanization process in order to let the rubber compound have chain relaxation. The usage of bio-based processing oil at low quantity refer as Part Per Hundred Rubber (PHR/PPHR) gives the high mechanical properties as the mineral processing oil (hydrocarbon oil) need to have higher phr amount to get the same value. In terms of tensile strength, sample 1 (EPO 5%) has the greatest value, which is 15.51 MPa, while sample 4 (GT 3000 5%) only has 13.17 MPa despite the fact that they both have the same phr loading. The exact same pattern could also be observed in the tear strength test that was carried out. The elongation at break value was found to be significantly different for samples 3 (EPO 13%) and 6 (GT 3000 13%), respectively. This is because of the plasticizer effect that the rubber processing oil has on the rubber compound, which becomes more noticeable as more rubber processing oil is loaded into the rubber compound. The elongation at break value was found to be 649.45% for sample 3 (EPO 13%) and 636.07% for sample 6 (GT 3000 13%).